A Mixed Encryption Algorithm Used in Internet of Things Security Transmission System - Xin, Mingyuan (2015 International Conference on Cyber-Enabled Distributed Computing and Knowledge Discovery, 2015)
Internet of things has be broadly applied for home, industry, and many other applications. For these applications, secure information transmission becomes a critical issue to ensure the system safety. Hybrid encryption technique is a new cryptographic paradigm and it can be applied to the Internet of Things. It provides the benefit of the symmetric key and asymmetric key performance. It enables strong security and low computational complexity. In this paper, we proposed a mixed encryption algorithm to provide information integrity, confidentiality, non-repudiation on the data transmission for Internet of Things. We demonstrate the security efficiency with the comparison with traditional encryption algorithms.